2010
DOI: 10.3109/17435390.2010.513836
|View full text |Cite
|
Sign up to set email alerts
|

Cellular recognition and trafficking of amorphous silica nanoparticles by macrophage scavenger receptor A

Abstract: The cellular uptake of engineered nanoparticles (ENPs) is known to involve active transport mechanisms, yet the biological molecules involved are poorly understood. We demonstrate that the uptake of amorphous silica ENPs by macrophage cells, and the secretion of proinflammatory cytokines, is strongly inhibited by silencing expression of scavenger receptor A (SR-A). Conversely, ENP uptake is augmented by introducing SR-A expression into human cells that are normally non-phagocytic. Confocal microscopy analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 38 publications
7
57
1
Order By: Relevance
“…We and others have shown that many metal oxide ENPs, including SiO 2 and Fe 3 O 4 , are internalized in macrophages via clathrin-dependent endocytosis involving macrophage scavenger receptors, such as SR-A. 7780 Most endocytic routes of ENP uptake converge within the lysosomal compartment, where acidic conditions can promote dissolution of ENPs and release of metal ions that exacerbate production of ROS. For many biopersistent ENPs, disruption of lysosome function can also trigger inflammasome activation and cell death through “protective” mechanisms, including autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that many metal oxide ENPs, including SiO 2 and Fe 3 O 4 , are internalized in macrophages via clathrin-dependent endocytosis involving macrophage scavenger receptors, such as SR-A. 7780 Most endocytic routes of ENP uptake converge within the lysosomal compartment, where acidic conditions can promote dissolution of ENPs and release of metal ions that exacerbate production of ROS. For many biopersistent ENPs, disruption of lysosome function can also trigger inflammasome activation and cell death through “protective” mechanisms, including autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the important role of macrophages as a first line of defense against foreign particulates, these experiments utilized the RAW 264.7 cell line as a model macrophage cell type that is commonly used for hazard assessment and mechanistic studies in nanotoxicology. 56,57 Dose-response analysis of the cytotoxic effects of AgNPs following 24-h exposure demonstrated that neither Ag pn 20 NP nor Ag Au 20 NP caused overt cytotoxicity at concentrations up to 25 lg/ml. However, a significant increase in cytotoxicity was observed at 50 lg/ml for both particle types, and this effect was exacerbated in particles containing a gold core.…”
Section: -9 Munusamy Et Almentioning
confidence: 99%
“…MARCO receptors have also been shown to interact with multiwalled carbon nanotubes, superparamagnetic iron oxide nanoparticles, and are also responsible for the uptake and intracellular accumulation of negatively charged 20 nm polystyrene nanoparticles [25, 29, 30] . Further, through silencing of SR-A receptors on macrophages, the uptake and inflammatory responses to amorphous silica nanoparticles has been inhibited [31] . The role of SR-A in silica nanoparticle uptake and responses was also demonstrated by overexpressing SR-A in non-phagocytic human embryonic kidney 293 (HEK293) cells, which do not normally express SR-A.…”
Section: Scavenger Receptor Class Amentioning
confidence: 99%
“…This resulted in increased silica nanoparticle uptake in HEK293 cells demonstrating a role for SR-A in NM uptake. To further confirm SR-A mediated silica nanoparticle uptake by macrophages, fluorescence confocal microscopy revealed intracellular colocalization of extracellular SR-A components and silica nanoparticles [31] . These studies taken together illustrate how the SR-A class of receptors can influence cellular uptake and specifically macrophage uptake of NMs (Table 1).…”
Section: Scavenger Receptor Class Amentioning
confidence: 99%